2006
DOI: 10.1007/s11664-006-0317-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and growth pattern transition of intermetallic compounds between Cu and Sn-3.5Ag containing a small amount of additives

Abstract: The morphology and grain growth pattern of intermetallic compounds (IMCs) formed between the Cu substrate and Sn-3.5Ag solder doped with a small amount of additive (0.1 mass%), say, Ni or Co, was investigated. After soldering, a duplex structure due to the additive discontinuity at the (Cu, Ni) 6 Sn 5 and (Cu, Co) 6 Sn 5 region was detected. That is, the outer area of the (Cu, Ni) 6 Sn 5 and (Cu, Co) 6 Sn 5 region on the solder side contained much higher Ni or Co additive concentration than the inner area on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…Recently, much attention has been paid to the effects of impurities and alloying additions on the Cu 6 Sn 5 interfacial reaction layers between the Snbased solders and Cu substrates. [1][2][3][4][5][6] Trace elements are categorised into two groups: [6] (1) elements that show marked solubility in the Cu 6 Sn 5 solder joint layer such as Ni, Sb, Au, In, Co, Pt, Pd, and Zn, and (2) elements that are not extensively soluble in Cu 6 Sn 5 such as Ag, Fe, Bi, Al, P, Ti, S, and rare-earth elements. The role of dissolved trace additions in Cu 6 Sn 5 in determining the intermetallic layer growth and phase stability has been the subject of a range of recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to the effects of impurities and alloying additions on the Cu 6 Sn 5 interfacial reaction layers between the Snbased solders and Cu substrates. [1][2][3][4][5][6] Trace elements are categorised into two groups: [6] (1) elements that show marked solubility in the Cu 6 Sn 5 solder joint layer such as Ni, Sb, Au, In, Co, Pt, Pd, and Zn, and (2) elements that are not extensively soluble in Cu 6 Sn 5 such as Ag, Fe, Bi, Al, P, Ti, S, and rare-earth elements. The role of dissolved trace additions in Cu 6 Sn 5 in determining the intermetallic layer growth and phase stability has been the subject of a range of recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Similarly, the Co additive in the Sn-based lead-free solders shows the same behavior. 13 In other words, the Cu 6 Sn 5 phase containing Co or Ni doping atoms can be labeled as (Cu,Co) 6 Sn 5 and (Cu,Ni) 6 Sn 5 , respectively. Regarding Ni solubility in the Cu 6 Sn 5 phase, Laurila et al have reported that a Cu 29 Ni 26 Sn 45 stable ternary phase can be formed after a long annealing time (up to 10,000 h).…”
Section: Introductionmentioning
confidence: 99%
“…The measured Co concentration in (Cu,Co) 6 Sn 5 , which is formed between Cu and Sn-3.5Ag solder containing a small amount of Co additive, is about 8.0 at.%. 13 It has been speculated that both (Cu,Co) 6 Sn 5 and (Cu,Ni) 6 Sn 5 phases possess a similar crystal microstructure to Cu 6 Sn 5 , in which Co or Ni atoms occupy the Cu atom sublattice. 4,5,13 However, the crystal microstructure of (Cu,Co) 6 Sn 5 and (Cu,Ni) 6 Sn 5 phases have not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additive elements included Ni, Sb, Co, Zn, Fe, Ge, rare elements, etc., while the components of the plating layer usually contain Ni, Ni-P, organic solderability preservative, and electroless nickel immersion gold (ENIG) plated on copper substrates. [1][2][3][4][5][6][7] However, little research has been devoted to the intrinsic characteristics of solder joints, especially solidification cracks in solder joints.…”
Section: Introductionmentioning
confidence: 99%